Optimalisasi Penerimaan Pajak Daerah di Kota Baubau: Analisis Implementasi Sistem Digital dan Peran Camat-Lurah - Haykal, Mohammad Iman; Utomo, Decky Dwi; Nalien, Elvira Mulya; Ardiensyah, Ardiensyah (Media Akuntansi Perpajakan, 2025)
Local taxes are one of the main sources of regional original revenue and play a crucial role in supporting development and public services in Baubau City. In response to the challenges of increasing tax revenue, the Baubau City Government has implemented a digital system for tax payments and optimized the role of district and sub-district officials as the front line in taxpayer outreach and data collection. This study aims to analyze the effectiveness of digital technology implementation and the involvement of local government officials in enhancing local tax revenue. The method used is a qualitative study with a policy analysis approach and literature review based on official government documents and reports on the implementation of the digital system. The results show that the use of QRIS-based payment systems and digital applications has facilitated citizens in fulfilling their tax obligations, improved transparency, and minimized tax leakage. Furthermore, district heads and sub-district leaders play a strategic role in raising awareness, collecting data, and reminding citizens about tax payments, thereby increasing public participation. The government has also adjusted tax rates and simplified administration through an integrated system, which has had a positive impact on increasing local tax revenue. Despite challenges such as limited infrastructure and digital literacy, these efforts represent a progressive step in local tax management in Baubau City. Moving forward, strengthening digital infrastructure and improving the capacity of local officials are essential to support the smart city vision and ensure sustainable tax revenue.